Pandangan Munif Chatib Tentang Multiple Intelligences Dalam Perspektif Pendidikan Islam - Astuti, Silvia; , Istanto, S.Pd.I., M.Pd (2017)
Islamic education is the process of preparing the younger generation to fill the role, to transfer knowledge and Islamic values. However, there are still manyschools that are lack in building potential and instilling Islamic values to students.Basides, in Indonesia there are still many schools which are predicated robotschools, strarting from the learning process systems. School target of success until at assessment system. To facilitate learners in nderstanding the matter oflearning, the teachers should a just their styles of teaching with those of learners'learning, and in recratment of learners, the school should receive them in anycondition because the job of school is to find learners' intelligences. MultipleIntelligences theory is found by Howard Gardner, this theory considers that everyhuman being has at least one intelligence in him self. Munif Chatib is one of theleaders of education in Indonesia to implement and develop the MultipleIntelligences theory. MunifChatib assess Multiple Intelligences theory in hisworks in the shaped of books.The problems studied in this thesis are "how does Munif Chatib viewmultiple intelligences" and "how does Munif Chatib view Multiple Intelligencesin the perspective of Islamic education". Meanwhile the objective of this research are to describe Munif Chatib's view on Multiple ntelligences and that his view inthe perspective of Islamic education. This research is the result of library researchby examining or reseaching soine books with the intent to obtain complete information. The reseach analysis using descriptive analytic techniques with theinductive method.After this research, the author obtains results that Munif Chatib inviewingmultiple intelligences there are nine intelligences of human and that intelligencewill continue to grow. Meanwhile Munif Chatib views multiple intelligences inthe perspective of Islamic education is as having three phases of development that need guidance and implanting Islamic education material. The systemimplemented in the school is input using multiple intelligence research, theprocess of using the MIR to formulate a lesson plan so that the students will easily understand the lesson and can produce a useful product, and output usingauthentic assessment that looks at them in three domains: cognitive, affective, andpsychomotor. The positive relationship that exists between parents and teachers make it easier to develop the students' physical and spiritual potential, so that theywill understand life and develop them selves as totre muslim personality.